Evaluating the efficiency of the synergistic effect in the business network - Dykan, Valeriia; Pakharenko, Oleksandr; Saienko, Volodymyr; Skomorovskyi, Andrii; Neskuba, Tetiana (Journal of Eastern European and Central Asian Research (JEECAR), 2021)
The article aimed to develop a methodology for monitoring the quality level of the synergistic effect of enterprises' economic activity in business network interaction on the example of mechanical engineering in Ukraine. Using the expert assessments of 386 senior and middle managers of 27 mechanical engineering enterprises of the Kharkiv region and the main components' method, the components of qualitative parameters of the synergetic effect of economic activity result from network interaction have been determined. An additive econometric model has been developed to calculate the integrated indicator of enterprises' economic activity's synergetic effect in terms of the business network of the studied enterprises. Using Fibonacci rules, the levels of qualitative component components and the integrated indicator of the synergy of economic activity in the context of a single network partner are determined.